Linagliptin for the treatment of Type 2 diabetes. (January 2014) - Tella, Sri Harsha; Akturk, Halis Kaan; Rendell, Marc
SUMMARY Linagliptin is a highly selective inhibitor of the enzyme DPP-4. It is one of several agents of this class now available for treatment of Type 2 diabetes. This review is based on a PubMed search, clinical trials and personal experience with linagliptin. In addition, the US FDA approval folder on linagliptin was obtained under the Freedom of Information Act and analyzed. The pharmacokinetics and pharmacodynamics of linagliptin are reviewed. The glucose-lowering effect of this agent is discussed both as a monotherapy and in combination with metformin, sulfonylurea, pioglitazone and insulin. The potential adverse effects of linagliptin are summarized. Linagliptin is an additional choice in the group of DPP-4 inhibitors. Unlike other DPP-4 inhibitors, linagliptin is excreted chiefly via the enterohepatic system and can be used without dose adjustment in patients with renal or hepatic impairment. As a group, the DPP-4 inhibitors have a relatively modest glucose-lowering effect. The primary use of DPP-4 inhibitors is in combination with other hypoglycemic agents, mainly metformin. Their principal advantage is a low incidence of hypoglycemia, making these agents desirable in patients such as the elderly and those with cardiac disease. A greater use of linagliptin and other DPP-4 inhibitors will occur if long-term studies show extended retention of insulin secretory capacity and/or reduced cardiac events over time with these agents.